Da'wah Activities, Imarah Management, and Administrative Challenges at the Tasikmalaya Grand Mosque - Andini Purna Dita; Ariana Suryorini (Munazzama: Journal of Islamic Management and Pilgrimage, 2026)
This research aims to identify the da’wah activities, the implementation of imarah management, and the challenges encountered by the management of the Tasikmalaya Great Mosque in promoting mosque prosperity. The study employs a qualitative research design using primary and secondary data collected through observation, interviews, and documentation to gain a comprehensive understanding of imarah management practices. The findings indicate that the mosque’s da’wah activities are designed to strengthen religious understanding, promote ethical values, and disseminate Islamic teachings. Programs such as Tabligh Akbar, regular religious study sessions, and various social activities encourage community participation, unity, and sustainable engagement among worshippers. The implementation of imarah management reflects systematic planning through surveys and discussions to identify the needs of the congregation and ensure effective organisation of mosque programs. However, the management faces several challenges, including inadequate planning, ineffective communication and coordination among administrators, limited participation from younger generations, and financial and maintenance constraints. The study concludes that regular program evaluation, continuous organisational improvement, and management and leadership training for mosque administrators are essential to enhance program effectiveness, strengthen institutional capacity, and support sustainable mosque prosperity.